"Getting your head out." The development of youth political militancy during the democratic transition in Resistencia, Chaco (1980-1983) (Quinto Sol, 2022)
In this article we analyze youth political militancy in the province of Chaco - Argentina during the period of recent history known as democratic transition, specifically from 1980 to 1983. We investigate the characteristics of youth groups, their members and the development of their political practices from the beginning of the decade until the advance of the electoral campaign.The results of the investigation, carried out from journalistic sources and oral interviews, allowed us to clarify the characterization of the "juvenile enthusiasm" assigned to the time. We recover aspects that led to the reorganization of political parties and influenced the scene of provincial political opening, stopping at the experience of youth groups. In this way, we incorporate aspects such as tensions with the recent past, relationships with senior leaders, and intergenerational political learning.
Keywords: democratic transition; activism; intergenerational experience; young people